2001
DOI: 10.1097/00003226-200111000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Enigma of the Abundant Water-Soluble Cytoplasmic Proteins of the Cornea

Abstract: It is accepted that the taxon-specific, multifunctional crystallins (small heat-shock proteins and enzymes) serve structural roles contributing to the transparent and refractive properties of the lens. The transparent cornea also accumulates unexpectedly high proportions of taxon-specific, multifunctional proteins particularly, but not only, in the epithelium. For example, aldehyde dehydrogenase 3 (ALDH3) is the main water-soluble protein in corneal epithelial cells of most mammals (but ALDH1 predominates in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 56 publications
6
48
0
1
Order By: Relevance
“…To date, genetic and molecular approaches have been at a loss to define the mechanisms regulating the dynamic variations in the differentiation that account for the structural specializations and symmetry of the transparent and refractile lens cell structure. Currently, the refracton hypothesis is the singular theory addressing the molecular genetics for transparency and refractive power of biological optics (Piatigorsky, 2001(Piatigorsky, , 2008. The cornerstone of the refracton hypothesis is that the lens and cornea accumulated diverse, taxonspecific multifunctional proteins by a gene sharing strategy, which contributed to the optical properties of both tissues.…”
Section: Discussionmentioning
confidence: 99%
“…To date, genetic and molecular approaches have been at a loss to define the mechanisms regulating the dynamic variations in the differentiation that account for the structural specializations and symmetry of the transparent and refractile lens cell structure. Currently, the refracton hypothesis is the singular theory addressing the molecular genetics for transparency and refractive power of biological optics (Piatigorsky, 2001(Piatigorsky, , 2008. The cornerstone of the refracton hypothesis is that the lens and cornea accumulated diverse, taxonspecific multifunctional proteins by a gene sharing strategy, which contributed to the optical properties of both tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Should the adduct also exist in ALDH3, covalent binding of NAD to the enzyme could provide a basis for enhancing the ability of ALDH3 to provide direct UV protection to the eye, as has been considered (48,49), or to maintain an added defense against products UV-induced lipid peroxidation (in addition to 4-hydroxynonenal) which could be directly deleterious to the thiol. At the moment, this remains conjecture, since no evidence has been found to suggest adduct formation in ALDH3.…”
Section: Discussionmentioning
confidence: 99%
“…19 -22 Since the expression of these proteins is similar to that of the lens, both in abundance and taxon specificity, it has been suggested that corneal crystallins play a role in determining the transparent and refractive properties of the cornea through a metabolic or structural function. 23 In support of this hypothesis, expression of corneal crystallins has been shown to be environmentally and developmentally regulated with a marked increase in expression after eyelid opening, exposure to light, and development of corneal transparency. 24,25 From the…”
Section: 11mentioning
confidence: 93%